ST. Apps: Six Together: Inovasi Sistem Rekomendasi Pelayanan Publik Rumah Ibadah di Indonesia Guna Menghasilkan Generasi Displin Ibadah - Rafles Ginting; Irvin Nicholas; Shelly Laravida; Fiqih Yusril (Universitas Pancasila, 2022)
ABSTRACT The Indonesian state guarantees freedom of religion for all its inhabitants. The fact that the initial precepts of Pancasila are spelled out as the basic concept of nation and state shows that this nation still views religion as a necessity. Man instinctively realizes the power in this life that is outside himself. This can be seen when humans face challenges in life, crises, and natural disasters. Man in general regrets and begs for help from whatever almighty is capable of saving him from his predicament. This is something that every human being faces. It is only natural that the Indonesian government should provide places, facilities or protection for every adherent of religion in this country. However, there are several obstacles found related to the desire to perform worship if you are outside the city, the presence of this application is expected to help people in Indonesia in recommending places of worship according to the nearest location.